Analisis Kelayakan Usaha Pembesaran Ikan Nila Salin (Oreochromis Niloticus) di Desa Sedari Kecamatan Cibuaya Kabupaten Karawang - Indrianto, Ariesni (Peneliti.net, 2024)
Sedari Village is an area that has quite good potential for cultivating saline tilapia The method used in this research is descriptive quantitative with a sampling technique using Purposive Sampling, namely a sampling technique with certain considerations and data collection is carried out by interviews, observation, literature study. The data obtained is processed using income analysis, BEP, and R/C ratio. Based on observation data, a calculation of costs is produced, these costs include an average variable cost of IDR 18,706,500/season. The average fixed costs are IDR 3,595,833/season, the average income received is IDR 27,900,000/season, the average income received is IDR 5,597,667/season, apart from the analysis of income and receipts, the data is also processed using Break Event Point analysis (BEP) and R/C ratio analysis. The business of rearing saline tilapia in brackish water ponds exceeds the break-even point, with a Production BEP of 5,932kg, Price BEP of IDR 14,388, and Revenue BEP of IDR 10,896,463. The business of rearing saline tilapia in brackish water ponds in Sedari Village, Cibuaya District, Karawang Regency has an R/C ratio of 1.25 so this business is declared feasible to operate and run.